ADAPTIVE SYNCHRONIZATION IN HIDDEN BROADBAND SYSTEMS - Grishentsev, A Y; Elsukov, A I (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2017)
Subject of Research. The paper deals with the method of adaptive synchronization in receiving devices of broadband communication systems of the hidden message exchange increasing the efficiency of computational capability usage of a receiving device. The research topicality is caused by the need in more effective usage of computing resources for accepting modules of broadband digital communication and radiolocation. Method. The proposed solution is an extension of sequential synchronization method being applied nowadays. The method consists of two synchronization stages: preliminary - hard, and subsequent - precise one. The entity of the proposed solution lies in computation of correlative function only in the area (window) near the expected central peak. The window movement along the accepted character sequence enables to find the actual peak position and to make synchronization. Decreasing of computing expenses is reached due to reduction of processed information volume. The method adaptivity is reached by exact retraining of synchronization during all communication session. The proposed solution is urgent for mobile systems of communication and radiolocation in condition of signal interference. Main Results. Simulation of synchronization system is carried out in the environment of Simulink (MATLAB). The signal created on the basis of a complex-valued matrix with the size equal to 3×4 with the special form of autocorrelation function is used as an example for synchronization. Model researches showed that the developed method enables to realize synchronization of transceiving system, without quitting the mode of the hidden (subnoise) message passing. It is shown that application of the developed method of the adaptive synchronization, gives the possibility to reduce significantly computational capability of a receiving device, necessary for synchronization. The number of operations in case of correlation function computation was decreased in 28 times as compared to a computation method in time over all range of counting and in 5 times concerning an algorithm of correlation function computation with the use of fast Fourier transform. Practical Relevance. Research results can find application in the design of receiving modules of broadband digital communication and radiolocation.